Situating sustainability : a handbook of contexts and concepts - Krieg, C. Parker; Toivanen, Reetta (HUP, Helsinki University Press, 2021)
Situating Sustainability reframes our understanding of sustainability through an emerging international terrain of concepts and case studies. These approaches include material practices, such as extraction and disaster recovery, and extend into the domains of human rights and education. This volume addresses the need in sustainability science to recognize the deep and diverse cultural histories that define environmental politics. It brings together scholars from cultural studies, anthropology, literature, law, behavioral science, urban studies, design, and development to argue that it is no longer possible to talk about sustainability in general without thinking through the contexts of research and action. These contributors are joined by artists whose public-facing work provides a mobile platform to conduct research at the edges of performance, knowledge production, and socio-ecological infrastructures. Situating Sustainability calls for a truly transdisciplinary research that is guided by the humanities and social sciences in collaboration with local actors informed by histories of place. Designed for students, scholars, and interested readers, the volume introduces the conceptual practices that inform the leading edge of engaged research in sustainability.